Quantitative surface fractography of alumina and alumina-SiC composites during diamond grinding - Merino, J; Cock, A; Roberts, S; Todd, R (2005)
It has recently been shown that small additions of SiC to alumina can significantly improve both the surface finish for a given grinding treatment, and the resistance to severe wear. This paper describes experiments designed to obtain a clearer understanding of the mechanisms involved by correlating quantitative measurements of surface fracture during a standard abrasive wear test with the wear rate for a range of microstructures. The surface fracture parameters measured were (i) the proportion of the surface in which pieces of material had been removed by brittle fracture, and (ii) the size (equivalent circular diameter and depth) of the individual pullouts. Microstructures with systematic variations in grain size, SiC volume fraction, SiC particle size, SiC position (inter- or intra-granular) and sintering aids were tested. The results indicate that the reduction in wear rate on adding SiC or. reducing the grain size is caused by a reduction in the area fraction of surface pullout by brittle fracture. For low SiC contents (similar to 2vol%), this reduction in surface pullout is a consequence of the reduction in size of the individual pullouts. For higher SiC contents (10vol%), there is evidence that the nucleation of surface cracking is also inhibited. The underlying micromechanisms responsible for these effects are discussed.